Diffusion bonding between Ti-6Al-4V alloy and microduplex stainless steel with copper interlayer - Eroglu, M; Khan, TI; Orhan, N (Maney Publishing, 2002)
In the present study, diffusion bonding was used to join Ti-6Al-4V alloy to a microduplex stainless steel using a pure copper interlayer. The effects of heating rate and holding time on microstructural developments across the joint region were investigated. After bonding, microstructural analysis including metallographic examination and energy dispersive spectroscopy (EDS), microhardness measurements, and shear strength tests were carried out. From the results, it was seen that heating rate and holding time directly affect microstructural development at the joint, especially with respect to the formation of TiFe intermetallic compounds, and this in turn affects the shear strength of the bonds. A sound bond was obtained with a heating rate of 100 K min(-1) and holding time of 5 min, and this was related to the small amount of TiFe intermetallics formed close to the duplex stainless steel side at this bonding condition. Although Ti2Cu and TiFe intermetallics were formed in all specimens, it was seen that the most deleterious intermetallic was TiFe. As the heating rate was decreased and holding time increased the amount of TiFe intermetallics increased, and consequently shear strength decreased. As a result, from the microstructural observations, EDS analysis, microhardness measurements, and shear strength tests, it was concluded that a high heating rate and a short holding time must be used in the diffusion bonding of Ti-6Al-4V to a microduplex stainless steel when pure copper interlayers are used.
Keywords: Superplastic Ti-6Al-4V